Ice nucleating activity of Pseudomonas syringae and Erwinia herbicola. - Kozloff, L M (1983)
Chemical and biological properties of the ice nucleating sites of Pseudomonas syringae, strain C-9, and Erwinia herbicola have been characterized. The ice nucleating activity (INA) for both bacteria was unchanged in buffers ranging from pH 5.0 to 9.2, suggesting that there were no essential groups for which a change in charge in this range was critical. The INA of both bacteria was also unaffected by the addition of metal chelating compounds. Borate compounds and certain lectins markedly inhibited the INA of both types of bacterial cells. Butyl borate was not an inhibitor, but borate, phenyl borate, and m-nitrophenyl borate were, in order, increasingly potent inhibitors. These compounds have a similar order of affinity for cis hydroxyls, particularly for those found on sugars. Lentil lectin and fava bean lectin, which have binding sites for mannose or glucose, inhibited the INA of both bacteria. All other lectins examined had no effect. The inhibition of INA by these two types of reagents indicate that sugar-like groups are at or near the ice nucleating site. Sulfhydryl reagents were potent inhibitors of the INA of both bacteria. When treated with N-ethylmaleimide, p-hydroxymercuribenzoate, or iodoacetamide, the INA was irreversibly inhibited by 99%. The kinetics of inactivation with N-ethylmaleimide suggested that E. herbicola cells have at least two separate ice nucleating sites, whereas P. syringae cells have possibly four or more separate sites. The effect of infection with a virulent phage (Erh 1) on the INA of E. herbicola was examined. After multiple infection of a bacterial culture the INA was unchanged until 40 to 45 min, which was midway through the 95-min latent period. At that time, the INA activity began falling and 99% of the INA was lost by 55 min after infection, well before any cells had lysed. This decrease in INA before lysis is attributed to phage-induced changes in the cell wall.